A Memória e a Transformação - A Quinta do Bom Gosto - Margarida Isabel Rio Travanca (2011)
In this thesis, "A Memória e a Transformação - A Quinta do Bom Gosto", I present a proposition for the restoration of a beautiful farm in Northern Portugal, near the Lima river. The development of the design is supported by a theoretical reflection, a set of theories and methodologies, in which different ideas and projectual paths intersect and relate to each other, aiming to clarify different methods of designing, instruments and operational tools. It is sought to undertake the project of restoration and transformation of a group of buildings with huge architectural and historic interest, Bom Gosto Estate, in Ponte de Lima, built in the end of the 19th century. The objective of this work is to find an adequate answer in the form of a project, based on a deep theoretical reflection and grounded in the historical interpretation of the setting and existing buildings. It's assumed that consistency and accuracy must underlie all tangible architectural designs and so this proposal is based on investigation and theoretical analyses. Thus, in a sort of intersection, the object of study leads to the theoretical research and the theory sets questions to the project. It's an exercise, an essay, which derives from a theme seldom studied in my course of studies - the intervention in historical buildings. So, in this way, this thesis seeks to deepen knowledge and contents that stimulate conscience while designing on the pre-existing. How can one deal with and solve this exercise? Which method will be more accurate? Restore? Substitute? Demolish? Expand? Conserve? Redraw? Preserve? The dissertation is divided into three parts. The first ,"Transforming Memory" presents a historical guideline on the topic of intervention on patrimony, a historical synthesis of different restoration theories and intervening approaches, placing the emphasis on the end of the 19th and the twentieth centuries. In the second chapter "Projecting Transformation", an attentive look upon four works of four different architects: two of them Portuguese - Álvaro Siza e Eduardo Souto de Moura - and two British - David Chipperfield and John Pawson. We have here an approach to different projecting procedures and working methods through the analyses of their choices while intervening in existent buildings, the way new architecture transforms what is ancient, how it accepts or dismisses the challenge of tradition, which references are used and how the solutions come about. The third, and last, chapter, "Memory and the Bom Gosto Estate Project", consists of designing a consistent project based on the reflections presented in the previous chapters. It's a less complex and more conceptual experiment, an opportunity to design something real, feasible, a script for a future intervention - who knows - and which concludes my cycle of studies.